Multicenter Randomized Controlled Trial Comparing the Contribution of Proxabrushes with Regular Toothbrushes and Only Regular Toothbrushes to the Oral Health of Thai Elderly. (31st March 2022) - Gururatana, Orachad; Vejvithee, Warangkana; Ekpatcha, Narisa
Abstract : Context . Poor oral hygiene results in oral diseases, potentially leading to serious consequences such as problems with chewing, biting, and swallowing in the elderly. In order to achieve good oral health, effective plaque control is vitally important. Objective . The aim of this two-group experimental study was to explore the effects of proxabrush on Thai elderly oral health. Design and Setting . Multicenter randomized controlled trial, parallel grouped, open label, blocked randomization was used at each province to allocate treatment. The study was conducted at public hospitals in 16 provinces in Thailand between November 2019 and January 2020. Methods . Participants in the test group used proxabrushes and regular toothbrushes, and participants in the control group used only regular toothbrushes for 6 weeks. Plaque accumulation, gingival status, and oral healthcare data were collected at baseline and at 6-week follow-up. Clinical oral health examiner was blinded to group assignment. Randomization was computer-generated, with allocation concealment by opaque sequentially number sealed envelopes. Data analysis compared plaque and gingival indices between the test and control groups. Results . A total of 510 elderly with at least 20 natural teeth and interdental spaces were randomized (test n = 255; control n = 255), and 35 were excluded from analysis because of early drop out leaving 239 in the test group and 236 in the control group. A sample of 475 aged between 60 and 91 years participated in the study; 158 (33.3%) were males and 317 (66.7%) were females. The results revealed that, compared to baseline knowledge, attitude and practice were improved at follow-up for both the test and control groups ( p < 0.05). At follow-up, the independent-samples t -test compares the test group plaque index mean of 0.49 (SD 0.44) to the control group mean of 0.60 (SD 0.56); a mean difference of 0.11 (95% CI 0.02 to 0.20) obtained demonstrated statistical significance ( p = 0.014), and comparing the test group gingival index mean of 0.52 (SD 0.50) to the control group mean of 0.65 (SD 0.60), a mean difference of 0.13 (95% CI 0.03 to 0.23) obtained demonstrated statistical significance ( p = 012). At follow-up, the test group had lower plaque accumulation and better gingival status than the control group. Gender, medical problems, educational level, occupation, and age were not different between the test and control groups. A combination of daily proxabrush and regular toothbrush use yielded significant benefits over regular tooth-brushing alone. Conclusions . In conclusion, proxabrush has been found to be an effective interdental cleaning aid among Thai elderly. This trial is registered with TCTR20220127004 .